Maize Genetic Resources Breeding Strategies and Recent Advances - Ahmed El-Esawi, Mohamed (IntechOpen, 2022)
Maize is one of the most economically important food crops worldwide. It is used for livestock feeds and human nutrition. Recent strategies have been adopted for improving maize crops. This book brings together recent advances, breeding strategies, and applications in the biological control, breeding, and genetic improvement of maize genetic resources. It also provides new insights and sheds light on new perspectives and future research work that have been carried out for further improvement of maize crops. This book is a useful resource for students, researchers, and scientists.